Pendekatan Swiss Cheese Model dalam Analisis Faktor Sistem dan Manusia terhadap Kejadian Patient Safety - Nurmaines Adhyka; Novia Zulfa Hanum; Intan Kamala Aisyiah; Tosi Rahmaddian; Elen Gusyulianti (Jurnal Pembangunan Nagari, 2026)
Patient safety implementation is an important indicator of hospital service quality. Organizational and individual factors contribute to the successful implementation of patient safety in nursing services. To analyze factors associated with patient safety implementation among inpatient nurses at Prof. HB. Saanin Psychiatric Hospital, Padang. An analytical observational study with a cross-sectional design was conducted from November 2023 to August 2024. A total of 98 nurses were selected using accidental sampling. Data were collected using a valid and reliable questionnaire and analyzed using univariate and bivariate analyses with the Chi-square test at a 95% confidence level. Good patient safety implementation was reported by 59.2% of nurses. Organizational factors (PR=4.00; 95%CI:1.95–8.21; p<0.001), supervisory factors (PR=1.91; 95%CI:1.12–3.27; p=0.019), preconditions for unsafe acts (PR=2.16; 95%CI:1.29–3.62; p=0.004), and unsafe acts (PR=2.16; 95%CI:1.27–3.67; p=0.005) were significantly associated with patient safety implementation. Organizational factors showed the strongest association, with nurses perceiving poor organizational support having a fourfold higher prevalence of poor patient safety implementation compared with those perceiving good organizational support. Organizational, supervisory, workplace, and individual factors are significantly associated with patient safety implementation. Strengthening patient safety culture, effective supervision, and improvement of work systems should be prioritized to enhance hospital service quality.